2014
DOI: 10.1245/s10434-014-4009-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-C Upregulates Cortactin and Promotes Metastasis of Esophageal Squamous Cell Carcinoma

Abstract: Upregulation of CTTN is critical for VEGF-C-mediated tumor growth and metastasis of ESCC. These finding suggest that VEGF-C upregulated CTTN expression through Src-mediated downregulation of miR-326. CTTN may be a crucial mediator of VEGF-C-involved ESCC metastasis, which provides a potential target for diagnosis and individualized treatment in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Furthermore, in our previous study it was demonstrated that SIX1, a developmental transcription factor predicted to represent a potential target gene of miR-23b-3p, may enhance the expression of VEGF-C in OS (2). VEGF-C promotes cervical cancer cell invasion and migration (48), and enhances the metastatic ability of esophageal carcinoma (49), whereas knocking down VEGF-C suppresses gastric cancer cell migration (50). Therefore, VEGF-C was investigated in the present study, and the results demonstrated that miR-23b-3p is associated with decreased expression levels of VEGF-C in U2OS cells.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, in our previous study it was demonstrated that SIX1, a developmental transcription factor predicted to represent a potential target gene of miR-23b-3p, may enhance the expression of VEGF-C in OS (2). VEGF-C promotes cervical cancer cell invasion and migration (48), and enhances the metastatic ability of esophageal carcinoma (49), whereas knocking down VEGF-C suppresses gastric cancer cell migration (50). Therefore, VEGF-C was investigated in the present study, and the results demonstrated that miR-23b-3p is associated with decreased expression levels of VEGF-C in U2OS cells.…”
Section: Discussionmentioning
confidence: 85%
“…Tumour angiogenesis involves not only the overexpression of angiogenic factors, but also the low expression of angiogenic inhibitors and an imbalance between the two (118). VEGF is an important pro-angiogenic factor and the most powerful pro-vascular endothelial growth cytokine that promotes cell division and vascular construction from esophageal cancer and ovarian cancer, increases microvascular permeability and promotes endothelial cell migration (119)(120)(121).…”
Section: Erk/mapk Signalling In Tumour Invasion and Metastasismentioning
confidence: 99%
“…Among these VEGF-VEGFR complexes, VEGF-C binds to both VEGFR2 and VEGFR3 and further enhances diverse biological effects, such as cell growth, proliferation, mobility and invasiveness, to promote angiogenesis, metastasis and tumor progression [1214]. Previous studies reported that activation of the VEGF-C/VEGFR3 signaling pathway increases cell migration and invasion to promote cancer metastasis, and a high expression level of VEGF-C has been correlated with the shortest survival time in lung cancer [10, 15] and esophageal squamous cell carcinoma [16, 17]. Elevated VEGF-C expression is also found in the lymph nodes of patients with metastatic melanoma [18].…”
Section: Introductionmentioning
confidence: 99%